Reaction of pyrroles with ethyl 2-nitroso- and 2-azo-propenoates, and with ethyl cyanoformate N-oxide: a comparison of the reaction pathways - Gilchrist, Thomas L. (1993)
The reaction of ethyl 2-nitrosopropenoate 2a with 1 -methylpyrrole, 2.5-dimethylpyrrole and 2.5- diphenylpyrrole has been investigated. In every case the products result from highly regioselective attack at C-2 of the pyrrole by the electrophile. The azopropenoate esters 2b and 2c react similarly with pyrroles, to the extent that even 1 -(triisopropylsilyl)pyrrole is attacked exclusively at the 2-position by the azo ester 2b. In contrast, the nitrile oxide ethyl cyanoformate N-oxide 12 reacts at the 3-position of 2.5- dimethyl- and of 2,5-diphenyl-pyrrole. The reactions of the nitroso and azo esters with pyrroles are interpreted as Diels-Alder cycloadditions with inverse electron demand.